Quantitative Sensory Changes Following Gasserian Ganglion Radiofrequency Thermocoagulation in Patients with Medical Refractory Trigeminal Neuralgia: A Prospective Consecutive Case Series - Huckhagel, Torge; Bohlmann, Lars; Westphal, Manfred; Regelsberger, Jan; Eichler, Iris-Carola; Hamel, Wolfgang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Objective Microsurgical vascular nerve decompression and percutaneous ablative interventions aiming at the Gasserian ganglion are promising treatment modalities for patients with medical refractory trigeminal neuralgia (TN). Apart from clinical reports on a variable manifestation of facial hypoesthesia, the long-term impact of trigeminal ganglion radiofrequency thermocoagulation (RFT) on sensory characteristics has not yet been determined using quantitative methods.Material and Methods We performed standardized quantitative sensory testing according to the established protocol of the German Research Network on Neuropathic Pain in a cohort of patients with classical (n = 5) and secondary (n = 11) TN before and after percutaneous Gasserian ganglion RFT (mean follow-up: 6 months). The test battery included thermal detection and thermal pain thresholds as well as mechanical detection and mechanical pain sensitivity measures. Clinical improvement was also assessed by means of renowned pain intensity and impairment questionnaires (Short-Form McGill Pain Questionnaire, Pain Disability Index, and Pain Catastrophizing Scale), pain numeric rating scale, and anti-neuropathic medication reduction at follow-up.Results All clinical parameters developed favorably following percutaneous thermocoagulation. Only mechanical and vibration detection thresholds of the affected side of the face were located below the reference frame of the norm population before and after the procedure. Statistically significant persistent changes in quantitative sensory variables caused by the intervention could not be detected in our patient sample.Conclusion Our data suggest that TN patients improving considerably after RFT do not undergo substantial long-term alterations regarding quantitative sensory perception.
Keywords: trigeminal neuralgia; thermocoagulation; lesioning; quantitative sensory; testing